DEFINITION OF THE ESSENCE OF THE CONCEPT "ENERGY SAVING" IN THE CONTEXT OF THE IMPLEMENTATION OF THE SUSTAINABLE DEVELOPMENT STRATEGY OF UKRAINE - N.O. Herasymenko (Економіка та право)
The article explores the essence of the concepts of "energy saving" and "energy efficiency". Based on the analysis of current legislation, the draft Law of Ukraine, reference and encyclopaedic sources and the European Union Energy Efficiency Directive, it is concluded that energy efficiency is a complex conceptual category that includes economic, innovative and environmental aspects. This concept can be considered in three dimensions: as an indicator of energy savings as a result of the application of certain measures; the property of the process of energy consumption (extraction, production, energy supply), which is determined by its quality and the amount of funds involved in the process; the relationship between the result achieved and the resources expended (energy) for its achievement (creation). And energy saving is the final result of a sequence of actions (technological, behavioral, economic and other) that allowed to get a reduction in energy costs while maintaining normal living conditions and reducing the negative impact on the environment. The generic concept of "efficiency" is analyzed. It is established that the term "productivity" is very close to the concept of efficiency, and in order to really evaluate the effectiveness of state policy in the sphere of using fuel and energy resources and energy conservation, it is worth paying attention to an important economic indicator — labor productivity. It was determined that energy saving and energy efficiency are central to ensuring a sustainable development strategy at both the national and international levels. The analysis of the conceptual apparatus of the topic under study demonstrates the need to improve the current domestic legislation in the sphere of energy conservation with the aim of bringing the regulatory and legal acts of the state in accordance with the provisions of the Directive of the European Parliament and of the Council of the EU 2012/27/EC "On Energy Efficiency" and the objectives of the New Global Strategy for Sustainable development.